A randomized trial comparing surgeon-administered intraoperative transversus abdominis plane block with anesthesiologist-administered transcutaneous block. (August 2018) - Narasimhulu, D.M.; Scharfman, L.; Minkoff, H.; George, B.; Homel, P.; Tyagaraj, K.
Highlights: Transversus abdominis plane (TAP) blocks decrease systemic morphine requirements. Randomized trial comparing surgical and conventional TAP blocks post-cesarean. Percutaneous TAP block performed by anesthesiologist using ultrasound. Surgical TAP block by surgeon under direct vision before closing fascia. Surgical TAP block takes less time and provides comparable postoperative analgesia. Abstract: Background: Injection of local anesthetic into the transversus abdominis plane (TAP block) decreases systemic morphine requirements after abdominal surgery. We compared intraoperative surgeon-administered TAP block (surgical TAP) to anesthesiologist-administered transcutaneous ultrasound-guided TAP block (conventional TAP) for post-cesarean analgesia. We hypothesized that surgical TAP blocks would take less time to perform than conventional TAP blocks. Methods: We performed a randomized trial, recruiting 41 women undergoing cesarean delivery under neuraxial anesthesia, assigning them to either surgical TAP block (n=20) or conventional TAP block (n=21). Time taken to perform the block was the primary outcome, while postoperative pain scores and 24-hour opioid requirements were secondary outcomes. Student's t-test was used to compare block time and Kruskal-Wallis test opioid consumption and pain-scores. Results: Time taken to perform the block (2.4 vs 12.1 min, P  <0.001), and time spent in the operating room after delivery (55.3 vs 77.9 min, P  <0.001) were significantly less for surgical TAP. The 24 h morphine consumption ( P =0.17) and postoperative pain scores at 4, 8, 24 and 48 h were not significantly different between the groups. Conclusion: Surgical TAP blocks are feasible and less time consuming than conventional TAP blocks, while providing comparable analgesia after cesarean delivery.